Cover Picture: Porosity‐Controlled Eggshell Membrane as 3D SERS‐Active Substrate (ChemPhysChem 8/2014). Issue 8 (6th June 2014) - Lin, Pei‐Ying; Hsieh, Chiung‐Wen; Tsai, Pei‐Chuan; Hsieh, Shuchen
<x xml:space="preserve">Abstract</x> S. Hsieh et al. present on p. 1577 a SERS platform comprised of a 3D porous eggshell membrane (ESM) scaffold decorated with Ag nanoparticles. ESM‐based SERS substrates exhibit a strong signal enhancement, biocompatibility, high pore density and good reproducibility.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>